Consumers' perception on security and risk of online electronic payment. - Loh, Evonne. (2008)
The objective of the research is to analyse the level of trust consumers in Singapore have in online payment systems. Through the survey findings, recommendations are made to areas that can help to improve the consumers' perception, and increase the volume of online payment transactions.